Biomass Accumulation and Carbon Storage in Six-Year-Old Citrus reticulata Blanco.Plantation - Mehta, Lal Chand; Singh, Jitendra; Chauhan, P. S.; Singh, Bhim; Manhas, R. K. (Indian Forester, 2016)
The potential of fruit trees to sequester carbon and thereby provide an environmental service remains unexploited. Although not fully understood, CO2 fixation in fruit orchards is probably higher in comparison to fixation in annual herbaceous crops. The present study was conducted in Jhalawar district of Rajasthan State, western India. A total of 7 trees were harvested to assess the biomass and carbon content in various parts of Citrus reticulata, and derive the allometric biomass equation for future research. The mean aboveground biomass was 10.05Â±0.03 Kg tree-1. The average aboveground allocation of biomass was nearly 76% and belowground biomass was 24%. The maximum carbon was stored by fruit biomass (2.10 Kg tree-1) followed by roots (1.42 Kg tree-1) and branches (1.11 Kg tree-1). Total carbon stored by 6 yr old C. reticulata plantation was 5.94 Kg tree-1 and 1.65 t C ha-1. A total of four biomass models were studied for developing a reliable equation for biomass estimation. All four models were found to be statistically significant (Ftest, P < 0.01) for all the aboveground and belowground plant parts, along with total biomass. Models with diameter as the only independent variable had less bias percentage (bias%) and percentage root mean square error (RMSE%) values than the models with diameter and height as the independent variables.